1993
DOI: 10.1111/j.1476-5381.1993.tb13533.x
|View full text |Cite
|
Sign up to set email alerts
|

l‐Arginine exerts a dual role in nociceptive processing in the brain: involvement of the kyotorphin‐Met‐enkephalin pathway and NO‐cyclic GMP pathway

Abstract: Intracerebroventricular (i.c.v.) administration of l‐arginine (l‐Arg), at 10–100 μg per mouse, produced antinociception in mice, as assessed by the tail flick test; this antinociception was reversed by pretreatment (s.c.) with naltrindole (NTI), a δ‐selective opioid antagonist, and by co‐administered l‐leucyl‐l‐arginine (Leu‐Arg), a kyotorphin (endogenous Met‐enkephalin releaser) receptor antagonist. l‐NG‐nitroarginine methyl ester (l‐NAME), a NO synthase inhibitor, but not d‐NG‐nitroarginine methyl ester, giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 32 publications
(34 reference statements)
3
50
1
2
Order By: Relevance
“…Besides, locally in the foot, Arg can increase the phase II response at low doses while higher doses can reduce the response. Discrepancies between these findings and our report may be due to the chronic application of NO precursor L-Arg at different doses here, or to some unkown factors, since NO has very complex effects, depending on its concentration, experimental methods, the system, and the cellular environment [4,6,15] .…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…Besides, locally in the foot, Arg can increase the phase II response at low doses while higher doses can reduce the response. Discrepancies between these findings and our report may be due to the chronic application of NO precursor L-Arg at different doses here, or to some unkown factors, since NO has very complex effects, depending on its concentration, experimental methods, the system, and the cellular environment [4,6,15] .…”
Section: Discussioncontrasting
confidence: 91%
“…Others report that NO produces dual effects on nociception, depending on the dose and the pain model [6] . Although many studies have demonstrated that NO precursor L-Arg exerts dual effects on nociception [4,5] , the Ge et al [14] have reported that inhibition of spinal NO production contributes to the antinociceptive effect of emulsified isoflurane on formalin-induced pain. Kolesnikov et al [1] also report that supraspinal administration of the NOS inhibitor NOArg or oligodeoxynucleotide targeting the 4 nNOS isoforms can suppress the formalin response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, NO synthase inhibitors, administered i.c.v., exhibit antinociceptive activity in the mouse, suggesting a nociceptive role of NO in the brain (Moore et al, 1991;Babbedge et al, 1993;Kawabata et al, 1993). It is unlikely that brain NO is involved in the production of the antinociceptive effect of L-Arg.…”
Section: Introductionmentioning
confidence: 99%